THU0114 Effects of smoking on baricitinib efficacy in patients with rheumatoid arthritis: pooled analysis from two phase 3 clinical trials. (15th June 2017) - Curtis, J; Emery, P; Burmester, G; Arora, V; Alam, J; Muram, D; Klareskog, L
Abstract : Background: The efficacy of some rheumatoid arthritis (RA) therapies is reduced among patients who are smokers. Objectives: This post-hoc analysis of two phase 3 studies assessed the effects of patient smoking status on the response to baricitinib treatment in patients with RA. Methods: In RA-BEAM (NCT01710358 ), patients with inadequate response to methotrexate were randomized to placebo once-daily (QD) (N=488), baricitinib 4 mg QD (N=487), or adalimumab 40 mg biweekly (N=330). 1 In RA-BUILD (NCT01721057 ), patients with inadequate response to conventional synthetic disease modifying antirheumatic drugs (csDMARDs) were randomized to placebo (N=228) or baricitinib (2 mg, N=229; or 4 mg, N=227) QD. 2 Patients continued background csDMARD therapy in both studies. This post-hoc analysis was conducted in the placebo (N=716) and baricitinib 4 mg (N=714) patients. Patient-reported smoking status was categorized as current (smokers) or not current (non-smokers). Results: Among 1, 430 evaluable patients who received placebo or baricitinib 4 mg, 290 (20.3%) were smokers. Smoking status at baseline did not affect the clinical results of treatment with baricitinib for 24 weeks; smokers who received placebo were numerically less likely than non-smokers receiving placebo to achieve most clinical outcomes (Table). Baricitinib's effect on modified total Sharp score was more pronounced among nonsmokers (interaction p-value =0.07). ACR20/50/70=20%, 50%, and 70% improvement in American College of Rheumatology criteria; CDAI=Clinical Disease Activity Index; DAS28-hsCRP=Disease Activity Score 28-high sensitivity C-reactive protein; HAQ-DI=Health Assessment Questionnaire-Disability Index; mTSS=modified total Sharp score; SDAI=Simple Disease Activity Index. Conclusions: This analysis of smokers and non-smokers in two RA trials demonstrated that the beneficial effect of baricitinib treatment versus placebo was similar on all clinical endpoints, but may differ for structural damage progression. References: Taylor PC et al. Arthritis Rheumatol 2015;67(suppl 10) abst 2L. Dougados M et al. Ann Rheum Dis 2017;76:88–95. Disclosure of Interest: J. Curtis Grant/research support from: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche/Genentech, Corrona, UCB, Myriad, Eli Lilly and Company, Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche/Genentech, Corrona, UCB, Myriad, Eli Lilly and Company, Employee of: University of Alabama at Birmingham, P. Emery Consultant for: Pfizer, MSD, Abbvie, BMS, UCB, Roche, Novartis, Samsung, Sandoz, Eli Lilly and Company, G. Burmester Consultant for: Eli Lilly and Company, V. Arora Employee of: Eli Lilly and Company, J. Alam Employee of: Eli Lilly and Company, D. Muram Employee of: Eli Lilly and Company, L. Klareskog Grant/research support from: Janssen, Pfizer, BMS, GSK, AbbVie, Roche.